Epstein-Barr Virus and Neurological Diseases - Zhang, Nan; Zuo, Yuxin; Jiang, Liping; Peng, Yu; Huang, Xu; Zuo, Lielian (Frontiers in Molecular Biosciences, 2022)
Epstein-Barr virus (EBV), also known as human herpesvirus 4,is a double-stranded  DNA virus that is ubiquitous in 90-95% of the population as a gamma herpesvirus. It exists in two main states, latent infection and lytic replication, each encoding viral proteins with different functions. Human B-lymphocytes and epithelial cells are EBV-susceptible host cells . Viruses cause latent  infection in B cells and nasopharyngeal epithelial cells throughout life in most immunologically  active individuals. EBV-infected cells, free viruses, their gene products, and abnormally elevated EBV titers in the cerebrospinal fluid can be found in the central nervous system. Studies have  shown that EBV can directly infect neurons or indirectly use infected B-lymphocytes, induce neuroinflammationand demyelinating changes, promote  proliferation, degeneration, and necrosis of glial cells, promote proliferative disorders of B- and T-lymphocytes, and contribute towards the occurrence and development of nervous system diseases,such as Alzheimer's disease,Parkinson's disease,  multiple sclerosis, acute cerebellar ataxia,  meningitis, acute disseminated encephalomyelitis, and brain tumors. However, the specific underlying molecular mechanisms are unclear. In this paper, we review the mechanisms underlying the role of EBV in the development of central nervous system diseases, which could bebeneficial in providing new research ideas and potential clinical therapeutic targets for neurological diseases.